Literatur Review : E-Learning Dan Aplikasinya Dalam Bidang Pendidikan Keperawatan - Koko Wahyu Tarnoto (Interest : Jurnal Ilmu Kesehatan, 2018)
Background: The development of information technology has an impact on the world of education in terms of learning systems. E-Learning (Electronic learning) is a webbased virtual education system that has the purpose of helping the process of teaching and learning activities. The method used in this literature study is the type of nonsystematic review. Method: The author searches for the electronic database PROQUEST, Science Direct, Elsevier, BMJ, Google Scholar and PubMed. The author also uses several search keywords namely "Virtual Learning", "Based Learning Avatar", "Nursing Education", Interactive Real Virtual Learning "," IPE "," IPC "," Interprofesional Collaboration "," Interprofessional Education "," Simulation Skills "by using boolean" AND. Results :"The author uses inclusion and exclusion criteria in conducting filtering articles published in 2013-2018. Conclusion:From the results It is known that E-learning and its various applications that have been applied in the world of nursing education can be used as alternatives in offering learning many benefits: Hope in the future e-learning will become more effective, along with the development of technology and learning methods used